(untitled) (Eurasian Journal of Philology Science and Education, 2021)
The article highlights the cognitive concepts of modern Kazakh poetry, defines philosophical knowledge, psychological attitude and aesthetic thoughts of the poet. Coded picturesin the poet’s mind are also studied and the meanings of poetic subtexts are revealed. The authors analyzed the works of E. Raushanov, M. Raiymbekuly, and J. Eleusiz, where guided by the concepts of cognitivism and manifested cognitive aspects in poetry. In contemporary Kazakh poetry, in matters of cognition, all the manifestations that appear in consciousness, through linguistics personalities, make up a number of cognitive concepts. The conceptual features of the intention and meaning considered separately, and the features of encoded concepts in the poet’s mind are studied. The signs of postmodernism in the poetry of modern poets appear with different details, and the structure of the poem has changed completely. The significant meaning and idea of the author, which wants to convey to the reader, is transmitted in a different way. The formation of linguistic units in poetry in form led to a discovery in modern literature. The frequent use of cognitive concepts and the ability of authors to convey ideas in a different form are common in modern poetry. Especially, in the process of development of modern Kazakh poetry, both prose and poetry are full of innovative searches. The article deals with these problems of modern Kazakh poetry, analyzes the work of modern poets.